Broad-spectrum physical fitness benefits of recreational football: a systematic review and meta-analysis. Issue 15 (25th January 2018) - Milanović, Zoran; Pantelić, Saša; Čović, Nedim; Sporiš, Goran; Mohr, Magni; Krustrup, Peter
Abstract : Background: A previous meta-analysis showed that maximal oxygen uptake increased by 3.51 mL/kg/min (95% CI 3.07 to 4.15) during a recreational football programme of 3–6 months in comparison with continuous moderate-intensity running, strength training or a passive control group. In addition, narrative reviews have demonstrated beneficial effects of recreational football on physical fitness and health status. Objective: The purpose of this systematic review and meta-analysis was to evaluate the magnitude of effects of recreational football on blood pressure, body composition, lipid profile and muscular fitness with reference to age, gender and health status. Design: Systematic review and meta-analysis. Data sources: MEDLINE, PubMed, SPORTDiscus, Web of Science, Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Google Scholar were searched prior to 1 February 2017. In addition, Google Scholar alerts were set up in January 2012 to identify potential papers with the following key terms: recreational football, recreational soccer, street football and street soccer. Eligibility criteria for selecting studies: Randomised and matched controlled trials with participants allocated to a recreational football group or any other type of exercises or passive control group were included. Training programmes had to last at least 2 weeks to meet the inclusion criteria. The primary outcome measures were blood pressure, resting heart rate, body composition, muscular fitness, and blood lipids and glucose tolerance. A total of 31 papers met the inclusion criteria and were included. Results: The effect of recreational football on systolic blood pressure (SBP) versus no-exercise controls was most likely extremely largely beneficial (effect size (ES)=4.20 mm Hg; 95% CI 1.87 to 6.53). In addition, a most likely very large beneficial (ES=3.89 mm Hg; 95% CI 2.33 to 5.44) effect was observed for diastolic blood pressure (DBP), when compared with non-active groups. Furthermore, a most likely extremely large beneficial effect was shown for SBP and DBP in participants with mild hypertension (11 and 7 mm Hg decrease, respectively) and participants with prehypertension (10 and 7 mm Hg decrease, respectively). Meta-analysis of recreational football determined the impact on resting heart rate as most likely extremely largely beneficial (ES=6.03 beats/min; 95% CI 4.43 to 7.64) when compared with non-active groups. The observed recreational football effect on fat mass was most likely largely beneficial (ES=1.72 kg; 95% CI 0.86 to 2.58) and the effect on countermovement jump (CMJ) performance was most likely very largely beneficial (ES=2.27 cm; 95% CI 1.29 to 3.25) when compared with non-active groups. Possibly beneficial decreases were found in low-density lipoprotein levels (ES=0.21 mmol/L; 95% CI 0.06 to 0.36). Possibly largely beneficial effect was observed for DBP in comparison with continuous running training. Small harmful and unclear results were noted for SBP, fat and lean body mass, body mass index, as well as muscular fitness when compared with running and Zumba training. Conclusion: The present meta-analysis demonstrated multiple broad-spectrum benefits of recreational football on health-related physical fitness compared with no-exercise controls, including improvements in blood pressure, resting heart rate, fat mass, low-density lipoprotein cholesterol and CMJ performance. Additionally, recreational football is efficient and effective as Zumba and continuous running exercise regimens with highlighted social, motivational and competitive components.